A Case Study of Procurement and Change Management in the Oil and Gas Industry in Malaysia - Tie, Ting Huat (2016)
The study suggests that supply chain integration (SCI) increases operational competencies. Over the past 34 years, highly integrated information exchange and strategic sourcing through SCI have been proven to be a major contribution to operational performance. The local Hook Up and Commissioning (HUC) service providers, however, have experienced at least a 15-year expansion since 2000 in Malaysia's oil and gas industry. Nonetheless, the SCI process within procurement and logistics operation is still considered incomplete. The focus here is to share some process of procurement from the logistics point of view such as cargo declaration documents during HUC project. An in-depth qualitative case study including interview, general field observation, and review of various types of documentation are employed to explore the actual practice of preparing the cargo declaration documents. All the collected data are analysed through the triangulation method. The findings of this study show that there is a high discrepancy of goods information in procurement and logistics documents due to inaccuracy of reporting by incompetent personnel. The main cause is the lack of sharing information from the point of procurement. The incomplete SCI thus reduces operation competencies and increases wastage. The uncontrollable operational wastage and current issues of oil-price crisis and other macro economy factors are causing the oil production cost to exceed the breakeven point. This study therefore is significant because it contributes to providing a framework for procurement change-management to improve overall operational performance particularly for HUC growth in Malaysia's oil and gas industry, including all other operation activities and services such as offshore drilling, subsea, installation, and other types of oil and gas operation.